Bringing a politics of hope to the tourism classroom: exploring an integrated curriculum design through a creative and reflexive methodology. (2nd January 2019) - Boluk, Karla A.; Muldoon, Meghan L.; Johnson, Corey W.
ABSTRACT: The university classroom as it has traditionally been structured is ill-equipped to prepare the creative, problem-solving, socially engaged, and ﬂexible young adults that today's employers demand. Hierarchical approaches to university education dominate, and students frequently fail to make the connections between what they are learning and real-world scenarios. In this paper, we present an Integrated Curriculum Design (ICD) project initiated by three professors at varying stages of their careers in two tourism classes in a Canadian University. While much of the scholarship on ICD to date has focused on its beneﬁcial aspects for students, here we employ Critical Analytic Practice (CAP) in order to critically reﬂect on our own pedagogic values, questions, and learning as we experienced them over the course of this project. Through our creatively reﬂective writings, we better understand how ICD has positively impacted our own ability to co-design and co-deliver meaningful learning experiences in the tourism classroom. Our research makes three contributions to:  the limited scholarship on ICD in tourism, the limited scholarship focused on reﬂexivity in tourism pedagogical scholarship and we draw attention to the use of CAP as an innovative way to represent data in tourism in order to broaden our audience and impact.